2005
DOI: 10.2337/diabetes.54.9.2779
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peripheral Blood CD14+ Monocytes Occurs in Diabetes

Abstract: Blood levels of inflammatory markers associated with endothelial dysfunction and atherosclerosis are increased in diabetic patients; the highest levels occur in poorly controlled diabetes. We investigated the activation state of peripheral blood monocytes in diabetes with respect to scavenger receptor (CD36) expression and monocyte chemoattractant protein-1, intracellular adhesion molecule-1, vascular cell adhesion molecule-1, and peroxisome proliferator-activated receptors mRNA expression. CD14؉ monocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 53 publications
7
81
1
2
Order By: Relevance
“…For instance, Rohde et al (27) showed that primary monocytes already express endothelial cell-specific markers such as vascular endothelial cell-cadherin (VE-cadherin; CD144) and endoglin (CD105), which substantiate the close relationship between these two cell types. Additionally, Cipolletta et al (28) recently showed that circulating CD14 ϩ monocytes express VCAM-1, which is congruent with our data (Table 1). In addition to the phenotypic overlap between monocytes and endothelial cells, two recent studies indicated that a subset of human peripheral blood monocytes can differentiate into several distinct mesenchymal lineages (29) as well as into T lymphocytes, epithelial cells, neuronal cells, and liver cells (30).…”
Section: Il-8 (4)supporting
confidence: 83%
“…For instance, Rohde et al (27) showed that primary monocytes already express endothelial cell-specific markers such as vascular endothelial cell-cadherin (VE-cadherin; CD144) and endoglin (CD105), which substantiate the close relationship between these two cell types. Additionally, Cipolletta et al (28) recently showed that circulating CD14 ϩ monocytes express VCAM-1, which is congruent with our data (Table 1). In addition to the phenotypic overlap between monocytes and endothelial cells, two recent studies indicated that a subset of human peripheral blood monocytes can differentiate into several distinct mesenchymal lineages (29) as well as into T lymphocytes, epithelial cells, neuronal cells, and liver cells (30).…”
Section: Il-8 (4)supporting
confidence: 83%
“…19,20 Moreover, ATM-induced inflammation has been associated with other co-morbidities such as cardiovascular diseases, liver steatosis or type 2 diabetes. 14,[21][22][23] Macrophages represent various cell populations with marked plasticity that mirror different functions depending on the stimuli that come from tissue microenvironment. [24][25][26] In mouse models, it has been reported that ATMs have reparative (remodeling) function with anti-inflammatory phenotype (known as M2-alternatively activated macrophages), whereas newly recruited macrophages activated during obesity are mainly pro-inflammatory (known as M1-classically activated macrophages).…”
Section: Introductionmentioning
confidence: 99%
“…However, metabolic disorders also appear to affect blood monocytes directly. A number of studies reported that monocytes both in patients with metabolic disorders and in dyslipidemic or diabetic mice undergo phenotypical and functional changes that may contribute directly to the development and progression of chronic inflammatory vascular diseases (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%